Os estudos de usuários nos programas de pós-graduação em ciência da informação do Nordeste - Simões, Angélica Clementino (2014)
The user studies have to focus on the use and behavior of people in relation to information. However, a number of studies with the theme user study " the same matter user information" without constitute an empirical study of groups of subjects taken from a relation of necessity, search and use information . Thus, this study aimed to map the academic production area Members Information Studies in the Graduate Program in Information Science Northeastern: Federal University of Bahia - UFBA, Federal University of Paraíba - UFPB and Federal University of Pernambuco - UFPE. Nature of quantitative and qualitative and descriptive, cut out as the universe studied 186 dissertations, which were analyzed from the following categories: type of users studied, worked thematic, often mentioned in the literature of approaches and methods and techniques of collecting and analyzing data. From the results obtained, it was observed that only 25 dissertations, a percentage of 13.44 % of searches made in PPGCI s NE constitute user study. These, mostly used alternative approaches, configured in exploratory and / or descriptive, nature of quantitative and qualitative research. As regards the instruments and data collection techniques, most made use predominantly of mixed questionnaire. So, can say that the research provided a deepening on user studies in the Graduate Program in Information Science in the Northeast and the results presented the practice of research and teaching in the disciplines of undergraduate and graduate in Information Science can be enriched.